Profile of Minimal and Non-Minimal Change Nephrotic Syndrome in Children: A Cross-Sectional Study - Jafar, Muh. Alfian; Rauf, Syarifuddin; Daud, Dasril (Fakultas Kedokteran Universitas Muslim Indonesia, 2020)
Introduction: Idiopathic nephrotic syndrome (INS) is the most common kidney disease in children. Histopathological features classify the disease into minimal change nephrotic syndrome (MCNS) and non-minimal change nephrotic syndrome (NMCNS). Clinical and laboratory characteristics are considered to be useful in estimating the underlying pathological changes. This study aimed to assess the spectrum of clinical and laboratory profiles in children suffering from MCNS and NMCNS. Methods: This was a cross-sectional study using medical records of patients hospitalized at Dr. Wahidin Sudirohusodo Central General Hospital and Hasanuddin University Teaching Hospital from January 2016 to August 2018. Subjects were classified into MCNS and NMCNS groups and evaluated for age, sex, hypertension, degree of edema, degree of hematuria, proteinuria level, cholesterol level, albumin level, urea level, and creatinine level. Data were analyzed by using chi-square, fisher's exact test Mann Whitney analysis, multivariate by logistic multiple regression analysis, and diagnostic test. Results: Of the 36 subjects enrolled, 10 (27.8%) had MCNS, and 26 (72.2%) had NMCNS. Bivariate analysis showed significant differences in hypertension (p=0.020; OR=12.3; 95% CI 1.35-111.61) and hematuria (p=0.018; OR=7.7 ; 95% CI 1.52-39.75). Multivariate analysis indicated that only hematuria is a significant predictor (p=0.014; OR=7.778; 95% CI 1.522 – 39.754). The diagnostic test of NMCNS showed hematuria sensitivity at 77% and specificity at 70% with a positive predictive value of 87% and a negative predictive value of 46%. Conclusion: Our study showed that hematuria is a sensitive predictor of NMCNS.